Sovereign CDS Spreads in Europe : The Role of Global Risk Aversion, Economic Fundamentals, Liquidity, and Spillovers - Heinz, Frigyes (IMF Working Papers; Working Paper ;, 2014)
By analysing data from January 2007 to December 2012 in a panel GLS error correction framework we find that European countries' sovereign CDS spreads are largely driven by global investor sentiment, macroeconomic fundamentals and liquidity conditions in the CDS market. But the relative importance of these factors changes over time. While during the 2008/09 crisis weak economic fundamentals (such as high current account decifit, worsening underlying fiscal balances, credit boom), a drop in liquidity and a spike in risk aversion contributed to high spreads in Central and Eastern and South-Eastern European (CESEE) countries, a marked improvement in fundamentals (e.g. reduction in fiscal deficit, narrowing of current balances, gradual economic recovery) explains the region's resilience to financial market spillovers during the euro area crisis. Our generalised variance decomposition analyisis does not suggest strong direct spillovers from the euro area periphery. The significant drop in the CDS spreads between July 2012 and December 2012 was mainly driven by a decline in risk aversion as suggested by the model's out of sample forecasts.